Application Of Design Of Experiment In Printed Cuircuit Board Assembly Industry. - Mathaeswari, V.; Safian, U.; Zalila, A. (2005)

(untitled)
Printed circuit board assembly (PCBA) is a process of mounting and inserting components to printed circuit board (PCB) by means of several principle processes such as Manual Insertion, Auto Insertion (Axial & Radial), Wave Soldering, Surface Mount Technology and Box Build. Manufacturers of PCBA are forced to produce better quality with less cost in order to stay in the business as globalization taking shape. To achieve such a goal, manufacturers are forced to strive to attain and maintain high first pass-yield.